2009
DOI: 10.1111/j.1751-7133.2009.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin‐Converting Enzyme Inhibitor or Angiotensin Receptor Blocker Therapy After Hospital Discharge on Subsequent Rehospitalization for Acute Myocardial Infarction and Heart Failure

Abstract: A n estimated 7.9 million persons in the United States have experienced acute myocardial infarction (MI) and 5.2 million have been diagnosed with heart failure (HF).1 MI and HF result in elevated morbidity and mortality risks and substantial economic burden.1,2 HF accounts for an estimated 1 million hospital stays annually, and $33.2 billion in direct and indirect costs to society annually. Direct and indirect costs to society for coronary heart disease, of which MI is a major contributor, is estimated at $162… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In previous reports age, gender, race, socioeconomic status, type of insurance, disease burden, weight, nutritional and functional status, length of stay, chronic diseases, and medication use and compliance have been identified as contributors to the likelihood of rehospitalization . Some of these factors have been incorporated in various prediction models that have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports age, gender, race, socioeconomic status, type of insurance, disease burden, weight, nutritional and functional status, length of stay, chronic diseases, and medication use and compliance have been identified as contributors to the likelihood of rehospitalization . Some of these factors have been incorporated in various prediction models that have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Three‐quarters of rehospitalizations ($44 billion yearly estimated cost) may be avoidable . Age, gender, race, socioeconomic status, type of insurance, disease burden, weight, nutritional and functional status, length of stay, chronic diseases, and medication use and compliance contribute to the potential for readmission . A screening tool for the detection of potential cases would likely make further case management more efficient, motivating efforts to develop reliable prediction models for risk of readmission …”
Section: Introductionmentioning
confidence: 99%
“…18 Based on these observations and that most evidence-based heart failure therapies that reduce hospital admission also reduce readmission, 19,20 we hypothesized that discharge prescription of digoxin will be associated with lower 30-day all-cause readmission in older heart failure patients hospitalized for acute decompensation. Therefore, the objective of the current study was to test the hypothesis that digoxin use is associated with lower 30-day all-cause hospital readmission.…”
mentioning
confidence: 99%
“…For example, Hess, Preblick, Hill, Plauschinat, and Yaskin (2009) found that ACE inhibitor or ARB postdischarge therapy for heart failure or acute myocardial infarction was associated with lowering of the rehospitalization risk for both heart failure and myocardial infarction. For example, Hess, Preblick, Hill, Plauschinat, and Yaskin (2009) found that ACE inhibitor or ARB postdischarge therapy for heart failure or acute myocardial infarction was associated with lowering of the rehospitalization risk for both heart failure and myocardial infarction.…”
Section: Demographic Clinical and Need Factors Associated With Hearmentioning
confidence: 99%